A Study on the Chain Ratio-Type Estimator of Finite Population Variance. (24th February 2014) - Olufadi, Yunusa; Kadilar, Cem
Abstract : We suggest an estimator using two auxiliary variables for the estimation of the unknown population variance. The bias and the mean square error of the proposed estimator are obtained to the first order of approximations. In addition, the problem is extended to two-phase sampling scheme. After theoretical comparisons, as an illustration, a numerical comparison is carried out to examine the performance of the suggested estimator with several estimators.